Seroprevalence and detection of H5N1 avian influenza virus in local chickens in Tabanan Regency, Bali, Indonesia - Gusti Ayu Yuniati Kencana; I Nyoman Suartha; I Made Kardena; Kadek Karang Agustina (Acta VETERINARIA Indonesiana, 2021)
Aim: Avian Influenza (AI) is a zoonotic disease that causes death in poultry and humans. Monitoring the virus needs to be carried out continuously to prevent outbreaks of the disease. Seroprevalence and detection of H5N1 and H9N2 AI virus antigen were intended to monitor the presence of viruses in local chickens in Tabanan, a Regency of the Indonesian island Province of Bali. The research aims were to detect the presence of H5N1 AI virus, and to know the distribution of this virus in Tabanan Regency. Materials and Methods: Research located in six districts of Tabanan regency namely Baturiti, Penebel, Marga, Kediri, Tabanan, and Kerambitan. A total of 1,398 local chickens that never been vaccinated with AI were randomly sampled in this study. The samples collected were serum, cloacal and tracheal swabs. Serum samples were tested with hemagglutination inhibition (HI) assay. While samples of cloacal and tracheal swabs were isolated in 9-day-old germinated chicken eggs, followed by hemagglutination assay and RT-PCR test using H5N1 and H9N2 primers. Results: AI seroprevalence in local chickens in Tabanan Regency was 1% with the distribution in each district as follows; Penebel 1.6%, Kerambitan 1.2%, Marga 1%, while Tabanan, Kediri, and Baturiti 0.7% each. H5N1 AI virus was detected in 11 samples, i.e. five in Marga district and three in Penebel district, two in Kediri, and one in Tabanan, while the H9N2 AI virus was not detected. Conclusion: These results indicate that H5N1 AI virus may still circulate in local chickens in Tabanan Regency, Bali.